2018
DOI: 10.3390/molecules23112888
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Cells of Bacillus circulans ATCC 21783 on Palm Curtain for Fermentation in 5 L Fermentation Tanks

Abstract: Palm curtain was selected as carrier to immobilize Bacillus circulans ATCC 21783 to produce β-cyclodextrin (β-CD). The influence for immobilization to CGTase activity was analyzed to determine the operation stability. 83.5% cyclodextrin glycosyltransferases (CGTase) of the 1st cycle could be produced in the 7th cycle for immobilized cells, while only 28.90% CGTase was produced with free cells. When palm curtain immobilized cells were reused at the 2th cycle, enzyme activities were increased from 5003 to 5132 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The cell density was 1.21 × 10 8 cells g -1 for cells immobilised for 24 h. While for cells immobilised for 48 h, the cell density was 1.71 × 10 8 cells g -1 . These results are in agreement with the work of the authors (Żur et al 2016;Wang et al 2018), who observed that cell immobilisation is a time-dependent process and they attribute this dependence to two main factors: cell multiplication and the formation of a strong and irreversible adhesion. The high cell load presented in this work can be attributed to the average size of supports and the immobilisation time.…”
Section: Counting Of Cells Adsorbed On the Supportsupporting
confidence: 93%
“…The cell density was 1.21 × 10 8 cells g -1 for cells immobilised for 24 h. While for cells immobilised for 48 h, the cell density was 1.71 × 10 8 cells g -1 . These results are in agreement with the work of the authors (Żur et al 2016;Wang et al 2018), who observed that cell immobilisation is a time-dependent process and they attribute this dependence to two main factors: cell multiplication and the formation of a strong and irreversible adhesion. The high cell load presented in this work can be attributed to the average size of supports and the immobilisation time.…”
Section: Counting Of Cells Adsorbed On the Supportsupporting
confidence: 93%
“…Bacillus subtilis and Bacillus amyloliquefaciens are widely used to produce fermented foods from soybeans and locust beans in Asian, and West African countries [17] [18]. Immobilized Cells of Bacillus circulans ATCC 21783 on palm curtain for fermentation and Daqu (a traditional fermentation starter for the production of baijiu and vinegar) and its derived products have been demonstrated [19] [20]. In addition Bacillus strains were further used as starters and tested for their ability to ferment several foods [21].…”
Section: Discussionmentioning
confidence: 99%
“…Eş et al (2016) and J. Wang et al (2018) demonstrated that the immobilization of Bacillus spp. on chitosan matrices and palm curtain, respectively, also led to improved CD production.…”
Section: Novel Approaches To Production and Application Of Cdsmentioning
confidence: 99%
“…Within a 10‐day period, immobilized B. firmus produced 5.8‐fold more β‐CD than free B. firmus , and immobilized B. sphaericus produced 4.3‐fold more β‐CD than free B. sphaericus (Moriwaki et al, 2014). Eş et al (2016) and J. Wang et al (2018) demonstrated that the immobilization of Bacillus spp. on chitosan matrices and palm curtain, respectively, also led to improved CD production.…”
Section: Using Fermentation And/or Enzymatic Treatments To Improve Fl...mentioning
confidence: 99%